CUSTOM RELAXATION INDUCED IMPURITY PHOTOCONDUCTIVITY IN THE UNITED AII BVI and AIII BV - L. B. Atlukhanova; F. S. Gabibov; M. A. Rizakhanov (Вестник Дагестанского государственного технического университета: Технические науки)
Two types of non-standard relaxation induced impurity photoconductivity (IIP) observed in photoconductors CdS, ZnSe, GaAs and others, depending on the kinetic characteristics of the traps are described. In one case, at the stage of post flashing monotonic decay which is typical for relaxation associated with slow traps (the ratio of the speed of the electron capture to the recombination rate (R << 1), the photo response is experiencing vibrations of low frequency (f =0.03-0.3Hz). Relaxation of the second type characterized by rapid photoelectric traps (R >> 1): measurement alternating signal (f > 20 Hz) relaxation curves take the form of curves usual impurity photoconductivity. Electronic processes responsible for relaxation of non-standard IIP are analyzed. For example, fast-centers, which include the characteristic AIIBVI donor Agi0, for the first time in semiconductors experimentally, investigated the dependence of the cross section of electron capture by traps energy released during localization.